2004
DOI: 10.1111/j.0956-7976.2004.00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Brains That Are out of Tune but in Time

Abstract: It is estimated that about 4% of the general population may have amusia (or tone deafness). Congenital amusia is a lifelong disability for processing music despite normal intellectual, memory, and language skills. Here we present evidence that the disorder stems from a deficit in fine-grained pitch perception. Amusic and control adults were presented with monotonic and isochronous sequences of five tones (i.e., constant pitch and intertone interval). They were required to detect when the fourth tone was displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
284
4
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 283 publications
(327 citation statements)
references
References 21 publications
31
284
4
5
Order By: Relevance
“…These processing algorithms are adequate for speech reception (Shannon, Zeng, Kamath, Wygonski, & Ekelid, 1995;Wilson et al, 2005), but they are inadequate for music (Kong et al, 2004;Leal et al, 2003). Interestingly, child implant users' musical limitations have parallels with those of musically disabled (amusic) but audiologically normal adults, who exhibit deficits in pitch processing but intact temporal processing (Hyde & Peretz, 2004;Murayama, Kashiwagi, Kashiwagi, & Mimura, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These processing algorithms are adequate for speech reception (Shannon, Zeng, Kamath, Wygonski, & Ekelid, 1995;Wilson et al, 2005), but they are inadequate for music (Kong et al, 2004;Leal et al, 2003). Interestingly, child implant users' musical limitations have parallels with those of musically disabled (amusic) but audiologically normal adults, who exhibit deficits in pitch processing but intact temporal processing (Hyde & Peretz, 2004;Murayama, Kashiwagi, Kashiwagi, & Mimura, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…While individual case studies of congenital amusia have pointed to fundamental deficits in pitch discrimination (Allen, 1878;Peretz et al, 2002), threshold-based testing in cohorts has yielded a mixed picture: Hyde and Peretz (2004) found that individuals with congenital amusia failed to detect a pitch change of a semitone when presented within the context of a five-item sequence that was otherwise monotonic and isochronous, while controls achieved ceiling performance for changes as small as 0.25 semitones. Foxton, Dean, Gee, Peretz, and Griffiths (2004) used forcedchoice methods to assess thresholds, separately for the detection of a pitch change and the discrimination of pitch change direction.…”
Section: Fine-grained Pitch Discriminationmentioning
confidence: 99%
“…Those with degraded perception of music-owing to a lack of sensitivity to pitch direction and/or a truncated window over which musical events can be integrated-may well be limited in the extent to which they can derive expectations from pitch. However, expectations can also be derived from temporal information (Hannon & Trehub, 2005), which is often preserved in congenital amusia (Hyde & Peretz, 2004). Alternatively, the extent to which appreciation of music is possible in the face of perceptual deficits may relate to whether or not there are accompanying deficits in the processing of timbre-a perceptual attribute concerning the quality of a sound.…”
Section: Experiential Aspects Of Music Listeningmentioning
confidence: 99%
“…For this reason, the majority of research into congenital amusia has investigated pitch-related processing, with findings indicating elevated thresholds in pitch change detection, pitch direction discrimination, and poor memory for pitch information (Foxton, Dean, Gee, Peretz, & Griffiths, 2004;Gosselin, Jolicoeur, & Peretz, 2009;Hyde & Peretz, 2004;Peretz et al, 2002;Tillmann, Schulze, & Foxton, 2009;Williamson, McDonald, Deutsch, Griffiths, & Stewart, 2010). Poor memory for timbral attributes has also been implicated although this deficit appears to be less severe compared to the pitch dimension (Tillmann et al, 2009).…”
mentioning
confidence: 99%